Additional file 1 of Pulsatilla Decoction and its bioactive component β-peltatin induce G2/M cell cycle arrest and apoptosis in pancreatic cancer - Wu, Rong; Xi, Zhichao; Liu, Mengfan; Ren, Hangui; Dai, Rongchen; Jiang, Xue; Nik Nabil, Wan Najbah; Wang, Yalin; Feng, Jiling; Chai, Qiong; Dong, Qihan; Xu, Hongxi (figshare, 2023)
Additional file 1: Figure S1. The composition and quality control of PD; Table S1. Composition of classical prescriptions; Figure S2. The cytotoxicity of 13 Chinese herbal formulae on pancreatic cancer cells; Figure S3. The cytotoxicity of podophyllotoxin and comparison of acute toxicity between β-peltatin and podo-phyllotoxin in mice.